Analysis of Public Transportation Competitiveness Based on Potential Passenger Travel Intentions: Case Study in Shanghai, China. Issue 4 (April 2019) - Li, Linbo; Cao, Mengfei; Bai, Yufang; Song, Ziqi
The primary goal of this paper is to identify the influence factors of public transportation (PT) competitiveness as related to potential passengers through an analysis of travel intentions. The logistic regression model is utilized to analyze PT travel intentions of people who commute daily by car in Shanghai, China. Through comparing the service quality of PT and of car from five aspects (i.e., comfort, timeliness, reliability, economics, and safety), the significant influence factors are identified. The results reveal that the difference in service quality between PT travel and car travel is insignificant for safety and convenience, while comfort, reliability, and economics matter most to the willingness to travel via PT. In addition, increasing the cost of car travel and improving the service quality of PT are both helpful in attracting car users to switch travel mode and enhancing PT competitiveness. The findings and suggestions will provide support to decisions in PT development policy making.